Pelatihan Financial Literacy Kepada Warga Di RT 002 / RW 028 Perumahan Buana Impian 2 Kel. Tembesi Kec. Sagulung - Kota Batam - Winnie Frisia; Sunarto Wage; Ronald Wangdra; Wasiman Wasiman; Syahril Effendi (Prosiding, 2023)
Community service activities are carried out in the form of training and coaching on financial literacy for residents in RT 002 / RW 028 Buana Impian 2 Housing, Tembesi Village, Sagulung District, Batam City. Based on the results of interviews in the field, it was found that many residents still did not know about financial literacy, namely how to manage personal finances, save, invest, and manage debt properly. The methods used in the training and coaching provided are the survey method, the lecture method, the discussion method and the exercise method which are carried out in 5 meetings. The residents were very enthusiastic about participating in the training and coaching conducted by the Batam Putera University Lecturer Team. The sustainability of the results of training and coaching activities is that it is hoped that residents will be able to manage their finances well.